PENERAPAN SISTEM INFORMASI PEMASARAN PADA USAHA KECIL MENENGAH (UKM) DI PURWOKERTO - Hidayah, Arini; Purnadi, Purnadi (Media Ekonomi, 2016)
This research, entitled "Implementation of Information Systems Marketing On Small and Medium Enterprises (SMEs) in Purwokerto". The purpose of this study was to determine the profile and the problems faced by SMEs in Purwokerto, and to investigate the role of local governments to SMEs in Purwokerto. The object of this study is the Small and Medium Enterprises in Purwokerto. Results from this study is an integrated website on SMEs in Purwokerto which contains information about the product, the company’s distribution network, promotional activities and direct sales company and product prices firm Keywords: Marketing, SME, Marketing and Information Systems Marketing